Modelo de Serious Game para Niños con Problemas de Aprendizaje: Caso de Estudio Problemas de Discalculia - Albán Taipe, Franklin Vinicio (2020)
Learning problems in young children in the school educational context are very common today, especially those related to the difficulty of solving problems that integrate numbers, basic concepts of quantities or the development of basic mathematical operations and that affect impairment. in the child's academic performance. The literature review allowed identifying serious game-related research aimed at solving learning problems in mathematics at the school stage. However, in general the analyzed works have not considered the integration of educational, psychological, pedagogical and therapeutic aspects that allow the design and construction of a serious game oriented to satisfy the needs of children. For this reason, a model is proposed for the design of a serious game for children with dyscalculia problems in children from 5 to 7 years of age in the Province of Cotopaxi, Canton Latacunga. To obtain the variables that enter the model, an online survey was applied that will allow knowing the perspective of experts related to the subject under study. Through the use of Logistic Regression, it was determined if the variables positively or negatively influence learning problems. For the development of the game, programming tools such as JAVA, MySQL and post-test were used. As a result, it is established that the academic, family, pedagogical and therapeutic aspects are statistically significant and can be considered by the designers of educational games in the analysis and design phase of the product, as well as the incorporation of elements of the engineering of software engineering and the integration of artificial intelligence as an emerging technology for the development of a technological tool to support children's teaching-learning processes